The Civil Responsibility towards Volunteerism: A Comparative Analysis Study - Yaseen, Hajar (Humanities Journal of University of Zakho, 2022)
Volunteerism is considered the social and global humanitarian activity. People around the world conduct volunteering work in different humanitarian aspects without expecting anything moral or material in return. Comprehensive researches in this field found out the major motives that motivated people to do volunteering work were religious and patriotic motives. In addition to this, volunteers do not even expect guidance, correction, or criticism since they are doing the volunteering work by their free will without expecting anything material. Based on this, an issue can be raised because the concept of volunteerism will be culturally misunderstood for its responsibility if it were not put within a legal frame. This is to say that volunteerism is as any other work in the community that can cause harms and can be entailed with responsibility. It is noticeable that volunteering work can cause practical problems which cannot be easily solved within the general provisions of civil law. The Iraqi legislation, as any other Arab country legislation, does not address this issue. It does not organize special laws to form volunteering work contract. Parallelly, the volunteerism, as work and activity, is not yet regulated by a civil law which legislators find it a loophole with the civil law. Thus, this paper attempts to shed lights on volunteerism as a concept and its types, significance, and consequences. Then, it states the civil responsibility that volunteering work covers. The results show indicate that the relationship between volunteers and the organization is based on civil contracts and it is prone to the regulations of the civil law. In accordance with the regulations and rules stated in the contract, the organizations are held accountable for any mistakes or harms that volunteers conduct. However, the organizations can deny the responsibility if they prove that they have given instructions and precautions to volunteers to avoid harms and damages or if it is proven that the damage is the result of some force majeure, a foreign cause, or a mistake of the injured party.